MIC breakpoints of XDR Enterobacterales Towards Polymyxin B, Colistin, and Tigecycline - Clinical Insights and Therapeutic Outcomes from A Descriptive Study - R. Kalaivani; Arunava Kali; Joshy M. Easow (Journal of Pure and Applied Microbiology)
The prevalence of antibiotic resistance among Gram-negative bacteria, particularly Enterobacterales, is rising. Extensively drug-resistant (XDR) Enterobacterales demonstrate nonsusceptibility to all except two or fewer classes of antibiotics, where it retains susceptibility to at least one agent. Besides tigecycline, colistin and polymyxin B are often the only available therapeutic options in developing countries. The aim of this study was to determine the susceptibility of XDR Enterobacterales to colistin, polymyxin B, and tigecycline by determining the MIC using microbroth dilution and analyzing the treatment outcome. A descriptive study was done at Mahatma Gandhi Medical College and Research Institute, Pondicherry, from May 2023 to July 2023. The study included non-ICU patients aged 18 years or older, who had infections caused by XDR Enterobacterales isolated from clinical specimens during the study period and provided informed consent. All quantitative measurement values in this study were analyzed using descriptive statistical methods. Colistin and polymyxin B MIC of 109 clinical isolates of XDR Enterobacterales were tested by microbroth dilution. Tigecycline MIC was determined for 73 of these isolates. Forty-eight patients received colistin or polymyxin B monotherapy and their treatment outcomes were documented. Out of the 109 XDR isolates, 16 (14.7%) were resistant to colistin, while 11 (10.1%) were resistant to polymyxin B. Tigecycline MIC values ranged from 0.06 µg/mL to 4 µg/mL. Successful treatment outcome was observed in 23.5% of patients with colistin and/or polymyxin B resistant isolates, whereas it was 70.9% in patients with colistin and polymyxin B intermediate isolates. The present study revealed that K. pneumoniae emerged as the predominant isolate among XDR Enterobacterales in our healthcare facility. Although only a small proportion of strains exhibited resistance to polymyxin B, colistin, and tigecycline, the treatment outcomes were notably poor in the case of colistin and/or polymyxin B resistant strains, underscoring the grave therapeutic limitations posed by these resistant pathogens.